PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Yahdi Pratama; Rita Dwi Putri; Nidia Anggreni Das (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
The phenomenon of the company's performance as happened to the banking company Citibank in March 2011. There was a burglary of funds by managers and tellers. The value of the stolen funds reached 17 billion. The suspect was a Citibank teller who abused Citibank's authority to manipulate data and transfer customer funds. The purpose of this study is to determine the effect of independent commissioners, audit committees, and managerial ownership and institutional ownership simultaneously on financial performance.This type of research is quantitative research to determine the effect of corporate governance (Independent Commissioner, Audit Committee, Managerial Ownership, and Institutional Ownership) on financial performance. The population in this study is the population in this study are banking companies listed on the Indonesia Stock Exchange for the 2017-2020 year and the samples taken in this study are annual financial statements taken from each financial report of each company for 4 years, namely 2017-2020 at banking companies that listed on the IDX.The test results show that independent commissioners have an effect on financial performance with t count 4.622 > t table value 19971 and significant 0.000 <0.05. The audit committee has no effect on financial performance with t count 1.571 < t table value 29971 and significant 0.121 > 0.05. Managerial ownership has no effect on financial performance with t count 0.326 < t table value 19971 and significant 0.267 < 0.05. Constitutional ownership has an effect on financial performance with t count 3,571 > t table value 19971 and significant 0.001 < 0.05. The results show that independent commissioners, audit committees, managerial ownership and institutional ownership simultaneously have an influence on financial performance with an F count of 16,662 with a significance level of 0.000, because the probability is much smaller than 0.05. Keywords: